Minat Berkunjung Ke Suku Baduy Sebagai Pengaruh Citra Destinasi dan Wisata Budaya - Henilia Yulita; Titi Widaningsih; Immanuel Kevin (UNIVERSITAS RAHARJA, 2024)
The Baduy tribe is an indigenous people who live in the interior of Banten, West Java. This study aims to explain and analyze the image of the destination and cultural tourism in influencing the intention to visit the Baduy tribal deepening village. Quantitative method used in this research. The research model uses structural modeling - partial least squares (PLS-SEM). This research analysis tool uses SMART PLS. The number of samples in this study were 112 respondents. The results of this study explain that destination image and digital marketing have a significant effect on purchase intention partially and simultaneously. The use of respondents with more diverse generations can be used to complement and enrich the results of this study.